1+√-(-5*-5) (-1*-1*-1)

The -5*-5 part is supposed to be -5 to the second power while -1*-1*-1 is supposed to be -1 to the third power. I just couldn't figure out how to type in exponents. Thank you!

Respuesta :

Answer:  The correct answer is:  " 6 " .

_______________________________________________

         { that is;  the simplified expression given is:  " 6" [positive 6].

_______________________________________________

Step-by-step explanation:

_______________________________________________

Given the expression;  which is intended to be:

_______________________________________________

    Simplify:     " 1 + √ [ - (-5²)( - 1³) ] " ?

_______________________________________________

Note:

Refer to "comments below" typed directly under 'where the question itself is asked' —for clarification.

_______________________________________________

First, solve and simplify the value under the square root sign:

_______________________________________________

- (-5²) (-1 ³) =  ?

   → (- 1)( - 5²) (- 1³)  = ?

    ↔  (- 5²)(- 1)( - 1³ )  = ?

  _______________________________________________

    - 5²  =  -5 * -5  = 25 ;  {Note:  A negative * a negative = a positive ).  

     →  Now, multiply this value by:  "(-1)" ;  

     (-1) * (25) =  -25 ;  

_______________________________________________

Now,   (-25) * (-1³)  = ?

_______________________________________________

Let us simplify:  " ( - 1 ³ ) " ;  

             " ( - 1³ )  =  (-1 * -1 * -1)  =  

                          ( -1 * -1) * -1  = ?  ;  

Note:  " (-1 * -1) =  1 (positive one) ;  

                   →  {since:  " a negative * a negative = a positive " .}.

               Then,  1 * (-1) =   -1  (negative one);  

      →  {since:  a "positive times a negative =  a negative"} ;  

_______________________________________________

So:   " ( - 1³)   =  - 1  " ;

So:  (-25) * (-1³)  =  (-25) * (-1) = 25 (positive 25) ;  

→  {since:  a "negative times a negative = a positive" ; and since:

" any value, multiplied by "1" ; results in that same original value."}.  

_______________________________________________

So, back to our problem:  

_______________________________________________

Simplify:     " 1  +  √ [ - ( - 5² ) ( - 1 ³ ) " ?

_______________________________________________

                               =    1   +  √25 ;  _______________________________________________

{Note that:  "√25 = 5 " ;   25 is a "perfect square";  

  since:  5² = 5 * 5 = 25 ;  and "25" is known as a "perfect square" ; since the square root of the non-zero positive integer  [in this case:  " 25 ") ;   results in a non-zero positive integer [in this case:  " 5 " .].

If not known by trial and error; or by common known knowledge, one may use a  calculator to find:  " √25 " ;  to get:  " 5 " .

_______________________________________________

 So:   We can write our original expression:

            "  1  +   [tex]\sqrt{25}[/tex] " ;

                     =  1   +  5  ;

                     =   6 .

_______________________________________________

The correct answer is:  " 6 " {positive 6}.

_______________________________________________

Hope this answer — and explanation — is helpful to you!

      Wishing you the best in your academic endeavors

                    — and within the "Brainly" community!

_______________________________________________